2018
DOI: 10.3390/molecules23061334
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Optimization of Medium for Pullulan Production by Aureobasidium pullulans NCPS2016 Using Fructose and Soybean Meal Hydrolysates

Abstract: Pullulan, with its excellent characteristics of film-forming, water solubility, and biodegradability, is attracting more and more attention in agricultural products preservation. However, high pullulan production cost largely restricts its widely application due to its low production. In order to improve pullulan production by Aureobasidium pullulans NCPS2016, the medium was optimized using single factor experiment and response surface methodology. Based on the single factor experiments, the contents of soybea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 27 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…It has also been claimed by many researchers that carbon source might be a significant factor in melanin pigmentation found in many strains of the microbe [28]. Sucrose, fructose, maltose, xylose, and glucose were the most common time and tested carbon sources for fermentative production of pullulan [29]. Through extensive study of the metabolic pathway of sucrose in pullulan fermentation, it was found that sucrose did not cleave into glucose and fructose in the medium [30,31].…”
Section: Substrate Optimization By the Ovat Approachmentioning
confidence: 95%
“…It has also been claimed by many researchers that carbon source might be a significant factor in melanin pigmentation found in many strains of the microbe [28]. Sucrose, fructose, maltose, xylose, and glucose were the most common time and tested carbon sources for fermentative production of pullulan [29]. Through extensive study of the metabolic pathway of sucrose in pullulan fermentation, it was found that sucrose did not cleave into glucose and fructose in the medium [30,31].…”
Section: Substrate Optimization By the Ovat Approachmentioning
confidence: 95%
“…In addition, the statistical optimization of the central composite design was applied for using molasses as a carbon source for pullulan production by A. pullulans , with a yield of 45 g/L [ 13 ]. A more recent study investigated the use of soybean meal hydrolysate as a nitrogen source and found that pullulan production by A. pullulans reached 59.8 g/L [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, genetic engineering methods can be time-consuming and expensive, and the stability of the modified strains can be a limitation. Optimization of the medium composition, as well as the different process parameters (e.g., temperature, pH, and agitation) for pullulan production by varying the level of each variable, can be challenging and have conflicting effects; this is due to the biosynthesis process needs an accurate balance of the fermentation conditions and very sensitive to the interactions among components [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The large and strong absorption band at 3436 cm −1 indicated the OH stretching vibrations in the pullulan structure [ 41 ]. The other strong absorption at 2924 cm −1 indicated an sp 3 C–H stretching vibration [ 42 ]. The peak at 1381 cm −1 confirmed the C–O–H bending at the C-6 position [ 43 ].…”
Section: Resultsmentioning
confidence: 99%